L-arginine-NO-cGMP signalling pathway in pancreatitis - Buchwalow, Igor (Nature Publishing Group, 2013)
The role of nitric oxide (NO) in the human pancreas and in pancreatitis still remains controversial. Furthermore, conflicting conclusions have been reached by different laboratories about the localization of the NO-generating enzyme (NO synthase, NOS) in the pancreas. Here, we investigated the co-expression of NOS with enzymes involved in regulation of NO signalling in the normal human pancreas and in pancreatitis. We found that the whole NO signalling machinery was up-regulated in pancreatitis, especially within the exocrine compartment. Furthermore, the exocrine parenchymal cells revealed higher levels of oxidative stress markers, nitrotyrosine and 8-hydroxyguanosine, in pancreatitis, which reflects the exceptional susceptibility of the exocrine parenchyma to oxidative stress. This study provides a direct link between oxidative stress and the enzymatic control of the NO bioavailability at the cellular level and endows with further insight into fundamental mechanisms underlying pancreatic disorders associated with disruptions in the L-arginine-NO-cGMP signalling enzyme cascade.